Prevalence of VP7 and VP4 Genotypes of Human Group A Rotavirus in Infants and Children with Acute Diarrhea in a Northern City of Bangladesh (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):190-7.The abstract of this article is available on the PubMed website